KEPUASAN KERJA DITINJAU DARI BEBAN KERJA KARYAWAN YANG BERLATARBELAKANG PENDIDIKAN TIDAK SESUAI DENGAN PEKERJAAN - Zuraida Zuraida (Jurnal Ilmiah Psyche, 2020)
Employees who are placed in positions that are not in accordance with educational backgrounds will experience a high workload so that they will feel dissatisfied at work. This study aims to examine the relationship between job satisfaction in terms of the workload of employees whose educational background is not appropriate for their work. Job satisfaction and workload variables are measured using a scale. The subjects of this study were 50 employees who work not according to educational background, with the determination of the sample based on accidental sampling. The analysis technique used in this research is quantitative analysis using Karl Pearson's product moment with the SPSS version 20 for Windows program. Based on the research results, it is known that job satisfaction has a negative relationship with the workload of employees with educational backgrounds that are not suitable for their work. There is a significant negative correlation (r-0.769 with sig <0.05) between the variable job satisfaction and the workload of employees whose educational background is not in accordance with their work, namely 0.000 and the significance value is below / smaller 0.05, this means that the lower the job satisfaction, then the higher the workload and vice versa, the higher the job satisfaction, the lower the workload. . Job satisfaction has the most low categories with a contribution of 56% and the workload at most has a high level category with a contribution of 58%.